Revitalizing lead-acid battery technology: a comprehensive review on material and operation-based interventions with a novel sound-assisted charging method - Juanico, Drandreb Earl O. (Frontiers in Batteries and Electrochemistry, 2024)
This comprehensive review examines the enduring relevance and technological advancements in lead-acid battery (LAB) systems despite competition from lithium-ion batteries. LABs, characterized by their extensive commercial application since the 19th century, boast a high recycling rate. They are commonly used in large-scale energy storage and as backup sources in various applications. This study delves into the primary challenges facing LABs, notably their short cycle life, and the mechanisms underlying capacity decline, such as sulfation, grid corrosion, and positive active material (PAM) degradation.We present an in-depth analysis of various material-based interventions, including active material expanders, grid alloying, and electrolyte additives, designed to mitigate these aging mechanisms. These interventions include using barium sulfate and carbon additives to reduce sulfation, implementing lead-calcium-tin alloys for grid stability, and incorporating boric and phosphoric acids in electrolytes for enhanced performance.In contrast, operation-based strategies focus on optimizing battery management during operation. These include modifying charging algorithms, employing desulfation techniques, and integrating novel approaches such as reflex and electroacoustic charging. The latter, a promising technique, involves using sound waves to enhance the electrochemical processes and potentially prolong the cycle life of LABs. Initial findings suggest that electroacoustic charging could revitalize interest in LAB technology, offering a sustainable and economically viable option for renewable energy storage.The review evaluates the techno-economic implications of improved LAB cycle life, particularly in renewable energy storage. It underscores the potential of extending LAB cycle life through material and operation-based strategies, including the innovative application of electroacoustic charging, to enhance the competitiveness of LABs in the evolving energy storage market.